Pedro Zulen and Peruvian Philiosophy in the early 20th century - Quintanilla, Pablo (2018)
Perdo Zulen (1889-1925) was a Peruvian philosopher who was influenced by Bergson’s French intuitionism, especially through Alejandro Deustua, as well as by American pragmatism, during a stay in Harvard University, where he familiarized himself with the works of Josiah Royce, Charles Sanders Peirce, and William James. This meeting of traditions, rather unusual at the time, enabled him to publish two books and many academic and journalistic articles of remarkable originality. This contribution seeks to present Zulen’s philosophical work and describe the Peruvian philosophical context in which it emerged.